2002
DOI: 10.1093/carcin/23.5.735
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of angiogenesis-related proteins synthesis by sodium butyrate in colon cancer cell line HT29

Abstract: Sodium butyrate (NaB), a short-chain fatty acid naturally present in the human colon, is able to induce cell cycle arrest, differentiation and apoptosis in colon cancer cells. In addition to these effects, we investigated the effect of NaB on two angiogenesis-related proteins in a colon carcinoma cell line (HT29): vascular endothelial growth factor (VEGF), the most potent angiogenic factor, and hypoxia-inducible factor (HIF)-1alpha, the main transcription activator of the VEGF gene, which are both constitutive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 17 publications
5
34
0
Order By: Relevance
“…Similarly, studies have also shown to inhibit the translocation of HIF-1a transcription in response to BuA-treatment [32]. We and others have previously shown the direct effect of BuA on VEGF and its receptors [31,28,29]. Consistent with the previous reports, our data demonstrate a dose-dependent inhibition of VEGF secretion in vivo.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Similarly, studies have also shown to inhibit the translocation of HIF-1a transcription in response to BuA-treatment [32]. We and others have previously shown the direct effect of BuA on VEGF and its receptors [31,28,29]. Consistent with the previous reports, our data demonstrate a dose-dependent inhibition of VEGF secretion in vivo.…”
Section: Discussionsupporting
confidence: 92%
“…The ability of BuA to modulate NF-jB activity may arise from its ability to inhibit histone deacetylases. The antiproliferative effect of BuA on transformed cells is well established, and it has emerged as an antiangiogenic agent by directly repressing the expression of angiogenic ligands or indirectly interfering with endothelial cell proliferation/enzymes required for angiogenesis [28][29][30]. We have previously shown that BuA could repress gene expression of VEGF/KDR systems in Ehrlich ascites tumor (EAT) cells in vitro [31].…”
mentioning
confidence: 99%
“…In addition, a recent publication by Pelizzaro et al (2002), show that butyrate induced a dose-dependent down-regulation of VEGF165 protein, a potent angiogenic factor and vis-à-vis up-regulates the hypoxia-inducible factor (HIF)-1a. Our reported effects on CD44 and the effects reported by our group previously (Barshishat et al, 2000) and by Pelizarro et al (2002) may induce altogether the significant effects induced by butyrate observed in vivo on metastatic formation. Nevertheless, the pan-deregulatory effect exerted by butyrate in the entire CD44 gene seems to play a key role in the complete abolishment of metastatic ability exhibited by HM7 cells.…”
Section: Experimental Therapeuticssupporting
confidence: 77%
“…Total mRNA was extracted by means of Trizol (Life Technologies, Frederick, MD) according to the instructions of the manufacturer. Reverse transcription-PCR amplification of VEGF-A and VEGF-C mRNA was carried out using the GeneAmp Gold RNA PCR reagent kit (Perkin-Elmer Biosystems, Foster City, CA) and the human VEGF-C PCR Primer Pair kit, respectively; samples were processed as described elsewhere (7). h-Actin was used as housekeeping gene and results were expressed as normalized densitometric units.…”
Section: Methodsmentioning
confidence: 99%